2019
DOI: 10.7595/management.fon.2019.0007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FDI Inflow on Average Wage and Employment in Serbia

Abstract: Research question: This research comes to examine the impact of FDI inflow on average wage and on employment in Serbia in the period 2005-2017. Motivation: FDI tendentiously increases the economic growth rates, taking into consideration the fact that developed economies benefit from FDI because their local institutions are more productive, while developing countries benefit from “pieces“ of FDI, i.e., dissemination of technology and rarely evoke some relevant progress in economic growth. Despite the growing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…As for the impact of FDI inflow on employment, Jude & Silaghi (2016) would provide an effective comparison with this research if the authors had used FDI inflow instead of FDI stock, because both the analyses claim the positive long-term effect on employment. The findings of this paper partially confirm the findings of Domazet (2016) as well, while disagreeing with Peric (2019), presumably because of the larger sample used in this research.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As for the impact of FDI inflow on employment, Jude & Silaghi (2016) would provide an effective comparison with this research if the authors had used FDI inflow instead of FDI stock, because both the analyses claim the positive long-term effect on employment. The findings of this paper partially confirm the findings of Domazet (2016) as well, while disagreeing with Peric (2019), presumably because of the larger sample used in this research.…”
Section: Discussionsupporting
confidence: 68%
“…According to them, FDI is responsible for the increase in wage inequality, as well, mostly due to the workers' skill levels. Whilst Sabic et al (2012), Zdravkovic & Martinovic (2016), Grahovac & Softic (2017), and Peric (2019) found that there is no significant impact of FDI inflow on employment, Stanisic (2008), and Jude & Silaghi (2016) claim that FDI inflow has a positive impact on employment growth. Similarly, Domazet (2016) stresses that FDI inflow represents only a partial contribution to employment rate growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The time aspect of the research of banking and macroeconomic indicators in the paper will cover the period 2010-2019 (at the quarterly level). The scientific goal of the research is to show whether and to what extent the state of banking and external components affects the performance of the BS in the WB, characterized by increased competition, business diversification and liberalization of capital movements [26] [27]. The research starts from the initial hypothesis (H1) which reads: "The trend of NPLs can be forecasted by creating predictive models that accept macroeconomic and BS performance indicators as components."…”
Section: Indroductionmentioning
confidence: 99%
“…To this context, the resurgence of foreign investors' interest was a matter of high importance for the government. Indeed in Bank International Trade Portal, 2019a;Perić, 2019).…”
Section: Inward Fdi In Serbia and Montenegromentioning
confidence: 99%
“…According to the location assessment tool, "fDi Benchmark," Serbia is one of the cheapest locations, especially for manufacturing (Shehadi, 2019). Perić, 2019). The business environment is highly bureaucratic, dominated by corruption and political interference, poor market reputation and low functioning of the rule of law.…”
Section: Inward Fdi In Serbia and Montenegromentioning
confidence: 99%